Efektivitas Senam Pinguin dan Yoga Kids Terhadap Peningkatan Kemampuan Motorik Kasar Pada Anak Usia 5 – 6 Tahun di RA Masyithoh V Kota Probolingg - Ima Amalia Juliyantiara; Dodik Hartono; Achmad Kusyairi (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The development of preschool children is crucial to monitor, as they are vulnerable to developmental deviations if not provided with proper stimulation. One essential aspect of development is gross motor skills, which involve movements of the whole body, particularly core muscle activities such as the arms and legs. This study aims to determine the effectiveness of penguin exercise and kids yoga on the development of children's gross motor skills. The research design used was a pre-experimental design with a two-group pre-post test model. The population consisted of 66 students from RA Masyithoh V in Probolinggo City, with 40 respondents selected using purposive sampling. Data collection included editing, coding, scoring, and tabulating. The instruments used were KPSP Observation Sheets, Standard Operating Procedures (SOPs), and activity modules. The data were analyzed using the Wilcoxon Signed Rank Test. The results showed significant differences in children's gross motor development before and after the implementation of penguin exercise and kids yoga, with a p-value = 0.000 (ρ < α = 0.005). The Z-value for pre-post penguin exercise was -4.379, while for pre-post kids yoga it was -4.134. These results indicate that penguin exercise is more effective in improving gross motor development in children. Movements in penguin exercise, such as opening wings, turning heads, flapping arms, and stomping, help stimulate various muscle groups. Meanwhile, kids yoga, when practiced regularly and with discipline from an early age, also positively contributes to the enhancement of gross motor skills in young children.